Creep characteristics of thermally-stressed Beishan granite under triaxial compression. (February 2023) - Liu, Jian-Feng; Luo, Xing; Feng, Gan; Zhou, Lu-Lin; Yang, Xing-Guo; Lu, Gong-Da
Abstract: The operation of enhanced geothermal system and geological disposal of radioactive waste typically involve considerable variations in the host rock temperature, and the resulting thermal damage induced by mismatched inter-mineralic expansion could hence modify fundamentally the mechanical rock behaviour. Despite tremendous efforts dedicated to the examination of quasi-static performance after temperature changes, the influence of thermal exposure on the rock response in the long term, however, has stilled remained largely unaddressed. In this study, a series of triaxial creep experiments are thus carried out over variably confined Beishan granite that has been thermally-stressed across a wide range of temperatures. The evolution of failure strain, creep rate, and long-term strength parameters with respect to thermal damage and confinement condition is then critically analyzed. Our experimental investigation suggests that the competition between thermal cracking and hydrostatic compaction could reshape radically the crystalline fabric and hence exert a decisive structural control over the resulting creep deformation. In particular, we have shown that a suitably configured residual crack network could contribute to apparent blunting of subcritical cracking and therefore enhance considerably the rock resistance to stress corrosion. Pervasive grain disintegration, however, stemmed from aggressive thermal treatment would otherwise eradicate effectively the favourable particle interlocking and hence weaken substantially the long-term rock stability. The authors believe the novel findings presented could refine the understanding of time-dependent rock deformation after experiencing intense thermal loading, and thus have significant implications for the reliable decarbonized electricity production towards delivering sustainable energy transition.